Tradhisi Kupatan di Desa Sumberejo Kecamatan Ambulu Kabupaten Jember (Tintingan Folklor) - Dzuhrotus Salwa Nafi’ah; Sukarman Sukarman (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Kupatan tradition in Sumberejo Village, Ambulu Sub-district, Jember Regency is a cultural heritage that has symbolic and religious meaning. This tradition initially developed as a form of gratitude and self-purification after the month of Ramadan, which was introduced through a cultural approach by Sunan Kalijaga. However, along with the times, the value and meaning of this tradition has shifted. This study examines the Kupatan Tradition from a folkloric perspective, with the aim of explaining (1) the origin of the Kupatan Tradition in Sumberejo Village, (2) the implementation of the Kupatan Tradition in Sumberejo Village, (3) the form and meaning of the equipment needed in the Kupatan Tradition in Sumberejo Village, (4) the function of the Kupatan Tradition in Sumberejo Village, (5) changes in the Kupatan Tradition in Sumberejo Village, (6) efforts to preserve the Kupatan Tradition. A descriptive qualitative approach was used in this research with interview, observation, and documentation methods as data collection techniques. The results of the data are oral and written, with research instruments in the form of researchers, questionnaires, observation sheets, and supporting tools. The results showed that the Kupatan tradition in Sumberejo village is The Kupatan tradition in Sumberejo village is held at Watu Ulo Beach on the seventh day of the month of Syawal as an expression of gratitude. Its performance is divided into two parts, namely the slametan and the procession of gunungan and pegon. The Kupatan tradition has been transformed into a procession, influenced by globalisation and modernisation, but also supported by the efforts of the Jember Tourism and Culture Office, which has made this tradition part of the Watu Ulo Pegon event. This research shows that the kupatan tradition not only functions as a cultural symbol, but also as a projection system, a validation of cultural institutions, a means of education, a means of monitoring norms, a means of strengthening local identity and a tourist attraction. Therefore, there is a need for synergy between the government, community and educational institutions in preserving this tradition so that its original values are maintained amidst the dynamics of changing times.